Implementation of Online Learning Based Quizizz for Identification of Difficult Concepts and Misconceptions in Buffer Material - Apriliana Drastisianti; Wiwik Kartika Sari; Dante Alighiri (Universitas Sebelas Maret, 2020)
This study aims to identify difficult concepts and misconceptions of buffer solution material during online learning. Basic Chemistry 2 course learning on buffer solution material is carried out online. The research subjects were 25 chemistry education students who took the Basic Chemistry 2 course for the 2019/2020 academic year. The research method used is descriptive. Data collection was carried out by providing multiple-choice tests using quizzes, a questionnaire to determine learning media, and an online learning process evaluation questionnaire. The results showed that the biggest difficult concept was the working principle concept of the buffer solution (92%). The misconceptions experienced by students are assuming that the reaction of acidic and alkaline solutions always produces a buffer solution, H2SO4 and SO42- are components of the buffer solution, the addition of strong acids to alkaline buffer solutions cause the solution to be neutral, and those that play a role in determining the pH of the buffer solution are weak acids / weak bases and their salts.